Thyroid dysfunction after irradiation - Błaszczyk, Piotr; Windorbska, Wiesława; Ziółkowska, Ewa; Bańkowska-Woźniak, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2005)
Purpose: The aim of our research was to estimate the frequency of biochemical and clinical hypothyreosis symptoms occurring in head and neck cancer or Hodgkin’s disease patients who underwent radical radiotherapy. Methods and materials: Our material comprised 64 larynx, oro- and laryngopharynx cancer patients as well as Hodgkin’s disease patients over 18 years old who were radically irradiated. The irradiated area included three levels of the neck lymphatic system and thyroid. Clinical symptoms as well as thyrotropin (TSH), triiodothyronine (T3) and thyroxine (T4) levels were estimated according to the irradiation dose in the period of 1-4 years after radiotherapy. Results: Biochemical symptoms of hypothyreosis were observed in 20.3% of patients. 14.1% of patients showed an increased thyrotropin level only and 10.9% of patients – a decreased thyroxine level. Clinical hypothyreosis symptoms were noted in 6.2% of irradiated patients. Hypothyroidism was more frequent in patients treated with radiotherapy after total laryngectomy. We observed an increased clinical and subclinical hypothyreosis risk according to an increased irradiation dose but biochemical and clinical hypothyreosis symptoms did not change significantly. Conclusions: 1. The depressed thyroid function is common after external radiotherapy for Hodgkin’s disease and cancers of the head and neck. Damage of the thyroid can develop in patients after radiotherapy when the organ is exposed to a radiation dose above 38 Gy. Routine testing for possible thyroid hypofunction before and after radiotherapy for head and neck cancer or Hodgkin’s disease should be included in the follow-up procedures.